Investigating the Impact of Surfactants on Protein Folding: Insights from AF₄, DLS and ProbeDrum - Johansson,Emelie (2024)
Today, proteins are used in a huge variety of industrial application ranging from detergents and pharmaceuticals to cosmetical products. Surfactants have the potential to increase solubility of poorly soluble protein, as well as hindering proteins in formulation to interact with the interface and thus protecting them from degradation. Even if the use of protein-surfactant system dates back decades and so does the research about them, there is no full understanding of the mechanism behind these system. In order to optimize its applications, a greater understanding of the protein-surfactant interactions need to be established. Surfactants naturally forms micelles in water, concealing their hydrophobic tails while exposing their hydrophilic heads. Depending on the charge of the surfactant, they are classified as ionic or non-ionic surfactants. Ionic surfactants tend to form micelles at a higher concentration compared to non-ionic surfactants. When combining ionic and non-ionic surfactants, they create mixed micelles. This phenomenon can be utilized by the addition of a non-ionic surfactant to a solution of a protein and an ionic surfactant. Studies have shown that this reverses protein denaturation, restoring the protein to its native and active state. The formation of mixed micelles prevents the ionic surfactant from binding to and denaturating the protein. However, while the reversal of protein denaturation by non-ionic surfactants have been proved with simpler proteins, its effectiveness with antibodies remains. In this report, addition of both ionic and non-ionic surfactant to an antibody solution was performed. Analysis of the solution with asymmetrical flow field-flow fractionation, dynamic light scattering, fluorescence spectroscopy and static light scattering confirms that this approach is also effective for the antibody, expanding its potential applications and lays the foundation for further optimization.
Keywords: pharmaceutical formulation; AF4; DLS; ProbeDrum; Trastuzumab; Surfactants; Micelles